2022
DOI: 10.1186/s12876-022-02293-y
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive enteral nutrition remodels the intestinal flora in patients with active Crohn's disease

Abstract: Background Although there are many hypotheses, the pathogenesis of Crohn's disease (CD) is not completely clear so far. Exclusive enteral nutrition (EEN) is a routine measure in the treatment of active CD. We aimed at investigating the impact of EEN on patients with active CD from microbial metabolomics. Methods 16S-rDNA sequencing technology and gas chromatography–mass spectrometer analysis were employed to investigate the modification of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
2
6
1
Order By: Relevance
“…A recent clinical trial demonstrated that the amelioration effects of exclusive enteral nutrition against Crohn's disease were in positive correlations with the intestinal abundance of Novosphingobium. 48 However, in our study, both Novosphingobium and Stenotrophomonas which were significantly enriched in mice of the HFD_ABX and L102 groups, were positively related to the abundance of intestinal Lactobacillus but may contribute to the oxidative stress in the liver and the damage of the intestinal barrier. Klebsiella was obviously enriched in the mice of the HFD_ABX and NC_ABX groups, and both L102 pectin and L13 pectin were able to significantly reduce the relative abundance.…”
Section: Discussioncontrasting
confidence: 60%
“…A recent clinical trial demonstrated that the amelioration effects of exclusive enteral nutrition against Crohn's disease were in positive correlations with the intestinal abundance of Novosphingobium. 48 However, in our study, both Novosphingobium and Stenotrophomonas which were significantly enriched in mice of the HFD_ABX and L102 groups, were positively related to the abundance of intestinal Lactobacillus but may contribute to the oxidative stress in the liver and the damage of the intestinal barrier. Klebsiella was obviously enriched in the mice of the HFD_ABX and NC_ABX groups, and both L102 pectin and L13 pectin were able to significantly reduce the relative abundance.…”
Section: Discussioncontrasting
confidence: 60%
“…Endoscopic indicators are considered the gold standard for measuring the activity of Crohn's disease; they are more often used in clinical trials to measure the effectiveness of various drugs with respect to induction and mainte- nance of mucosal healing. The most common assessment systems used to measure the clinical activity of the disease include the Crohn's Disease Activity Index (CDAI), the Harvey-Bradshaw Index (HBI) and the Short Questionnaire on Inflammatory Bowel Diseases (SIBDQ) [25][26][27][28][29]. The Crohn's Disease Activity Index is a research tool used to quantify the symptoms of Crohn's disease patients.…”
Section: Crohn's Diseasementioning
confidence: 99%
“…The Harvey-Bradshaw Index was developed in 1980 as a simpler version of CDAI for data-collection purposes. It consists only of clinical parameters: general well-being (0 = very good, 1 = slightly below aver- The Short Questionnaire of Inflammatory Bowel Diseases is a widely used tool for assessing the quality of life associated with health in patients with IBD [25][26][27][28][29]. Treatment of Crohn's disease is considered as a developing problem due to its widely heterogeneous manifestations, coincidence of characteristics with other inflammatory diseases, often elusive extraintestinal manifestations, and uncertain etiology.…”
Section: Crohn's Diseasementioning
confidence: 99%
See 2 more Smart Citations